Roles of EvpP in Edwardsiella piscicida-Macrophage Interactions - Qin, Lei; Wang, Xingqiang; Gao, Yingli; Bi, Keran; Wang, Weixia (Frontiers in Cellular and Infection Microbiology, 2020)
Edwardsiella piscicida is found to be an important facultative intracellular pathogen with a broad host range. These organisms can replicate and survive within host macrophages to escape from the subversion of the immune defense. E. piscicida-macrophage interaction is very important in determining the outcome of edwardsiellasis. As an effector protein of E. piscicida T6SS, EvpP has been determined to be a very important virulence factor for E. piscicida, although its precise role in E. piscicida-macrophage interactions is not yet clear. In this study, the roles of EvpP in E. piscicida-macrophage interactions were characterized. Here, we constructed the deletion mutants of evpP (ΔevpP) and complementation (ΔevpP-C) by the allelic exchange method. Compared to wild type strain (WT), ΔevpP was found to be attenuated for growth within macrophages. In line with this observation, we found its survival capacity was lower than WT under oxidative and acid stress in vitro, which simulate conditions encountered in host macrophages. Attenuation of ΔevpP also correlated with enhanced activation of macrophages, as reflected by augmented NO production in ΔevpP-treated macrophages. Moreover, compared to WT, ΔevpP induced markedly increased apoptosis of macrophages, characterized by increased Annexin V binding and the activation of cleaved caspase-3. These findings provided strong evidence that EvpP is involved in the process of E. piscicida-macrophage interactions and is required for its survival and replication in macrophages. Thus, we propose that EvpP might be an important factor that controlling the fate of E. piscicida inside macrophages. To further exploring the underlying mechanism of EvpP action, the cDNA library was constructed from E. piscicida-infected macrophages and a yeast two-hybrid screen was performed to search for cellular proteins interacting with EvpP. Ribosomal protein S5 (RPS5) was identified as a target of EvpP. Furthermore, the interaction was validated with co-immunoprecipitation assay. This result implies that the observed effect of EvpP on macrophages might be related to RPS5-mediated regulation, contributing to a better understanding of the mechanisms of EvpP involved in E. piscicida-macrophage interactions.